2022
DOI: 10.1007/s00300-022-03074-9
|View full text |Cite
|
Sign up to set email alerts
|

Summer temperature—but not growing season length—influences radial growth of Salix arctica in coastal Arctic tundra

Abstract: Arctic climate change is leading to an advance of plant phenology (the timing of life history events) with uncertain impacts on tundra ecosystems. Although the lengthening of the growing season is thought to lead to increased plant growth, we have few studies of how plant phenology change is altering tundra plant productivity. Here, we test the correspondence between 14 years of Salix arctica phenology data and radial growth on Qikiqtaruk–Herschel Island, Yukon Territory, Canada. We analysed stems from 28 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 125 publications
(241 reference statements)
0
2
0
Order By: Relevance
“…To our surprise, even over 7 years of snow manipulation, altered snowmelt timing had hardly any effects on the vegetation. Several studies in arctic tundra and alpine vegetation observed a similar unresponsiveness in productivity to earlier snowmelt, both above-and below-ground (Baptist et al, 2010;Boyle et al, 2022;Darrouzet-Nardi et al, 2019). It was previously argued that adverse effects of freezing temperatures during earlier snowmelt outweigh beneficial effects of a longer growing season (Wipf et al, 2009) but particularly graminoids exhibit a high freezing resistance even in a fully active state (von Büren & Hiltbrunner, 2022).…”
Section: Weak Effects Of Snowmelt Timingmentioning
confidence: 83%
See 1 more Smart Citation
“…To our surprise, even over 7 years of snow manipulation, altered snowmelt timing had hardly any effects on the vegetation. Several studies in arctic tundra and alpine vegetation observed a similar unresponsiveness in productivity to earlier snowmelt, both above-and below-ground (Baptist et al, 2010;Boyle et al, 2022;Darrouzet-Nardi et al, 2019). It was previously argued that adverse effects of freezing temperatures during earlier snowmelt outweigh beneficial effects of a longer growing season (Wipf et al, 2009) but particularly graminoids exhibit a high freezing resistance even in a fully active state (von Büren & Hiltbrunner, 2022).…”
Section: Weak Effects Of Snowmelt Timingmentioning
confidence: 83%
“…As biomass production may correlate with growing season length (Kudo, 1992), earlier snowmelt was expected to enhance productivity (Rammig et al, 2010). However, experimental studies have provided little evidence of a stimulating effect of earlier snowmelt on biomass production so far (Baptist et al, 2010; Boyle et al, 2022; Darrouzet‐Nardi et al, 2019; Möhl et al, 2022; Wipf et al, 2009). On the other hand, drought periods are known to reduce above‐ground biomass production in different grassland types (Kahmen et al, 2005; Kröel‐Dulay et al, 2022; Mackie et al, 2019), including subalpine meadows (Gilgen & Buchmann, 2009; Ingrisch et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Betula pubescens growth appears to be little affected by precipitation. Studies in Iceland (Levanič and Eggertsson, 2008), Finland (Welling et al, 2004), and Sweden (Kullman, 1993) have shown that temperature is the significantly more decisive growth parameter (Boyle et al, 2022). Nevertheless, an approximate precipitation minimum can be inferred from the present distribution of the species in the subarctic regions of the Northern Hemisphere.…”
Section: Effects Of Reconstructed and Modern Humidity And Precipitati...mentioning
confidence: 96%
“…Nutrient supply is one of the three major growth-limiting factors for modern Betula sp. at high latitudes along with temperature and precipitation (Boyle et al, 2022;Weih and Karlsson, 1997). While temperature and precipitation during the Late Glacial-Early Holocene can be approached via robust proxy data, the assessment of nutrients in the soil remains a matter of estimation.…”
Section: Nutrient Supplymentioning
confidence: 99%
See 1 more Smart Citation